2018
DOI: 10.1111/asj.13034
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term ingestion of deoxynivalenol in naturally contaminated feed alters piglet performance and gut hormone secretion

Abstract: The mycotoxin deoxynivalenol (DON) generally exists in cereals and affects human and animal health. The aim of this study is to analyze the impacts of DON in naturally contaminated feed on piglet growth performance and intestinal hormone secretion in the short term. We randomly divided 5-week-old piglets into four groups: Control, DON 1,000, DON 2,000 and DON 3,000 groups. Piglets received a feed naturally contaminated with DON (approximately 400, 1,000, 2,000 or 3,000 μg/kg) for 21 days. Body weight showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The adverse effects on intestinal morphology in various in vivo models have been recorded for different mycotoxins such as AFs [ 99 , 103 , 104 ], OTA [ 107 ], and DON [ 72 , 114 , 115 , 116 , 117 ]. In addition, a variety of clinical chemistry analytes such as urine, feces, and blood may also reflect defects in intestinal barrier function in vivo (e.g., fatty acid-binding protein and C-reactive protein levels in serum, and fecal hemoglobin and fecal calprotectin) [ 130 , 131 ].…”
Section: Intestinal Dysfunction Induced By Mycotoxinsmentioning
confidence: 99%
“…The adverse effects on intestinal morphology in various in vivo models have been recorded for different mycotoxins such as AFs [ 99 , 103 , 104 ], OTA [ 107 ], and DON [ 72 , 114 , 115 , 116 , 117 ]. In addition, a variety of clinical chemistry analytes such as urine, feces, and blood may also reflect defects in intestinal barrier function in vivo (e.g., fatty acid-binding protein and C-reactive protein levels in serum, and fecal hemoglobin and fecal calprotectin) [ 130 , 131 ].…”
Section: Intestinal Dysfunction Induced By Mycotoxinsmentioning
confidence: 99%
“…Following ingestion of contaminated food or feed, the intestinal tract is the primary target of DON. Some studies demonstrated that exposure to DON could destroy the integrity of the intestinal barrier and the protein structure of intestinal epithelial cells, thus causing oxidative stress, inflammation and apoptosis (De Walle et al, 2010; Li et al, 2018; Yu et al, 2017). IPEC‐J2 is commonly utilized to analyze the transport function of intestinal epithelium and study the influence of nutrients or toxins on intestinal function (Brosnahan & Brown, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of DON varied according to several parameters such as the dose, the duration of exposure, the animal age as well as nutritional factors [ 39 ]. Previous studies reported negative impacts on the performance and gut hormone secretion of naturally mycotoxin-contaminated feed for piglets (1 to 3 mg/kg) during a 21 day-period [ 40 ]. In addition, gut health and integrity were affected in 6-week-old growing pigs with a low dose (0.9 mg/kg feed) for 10 days [ 38 ].…”
Section: Discussionmentioning
confidence: 99%